Sistem Informasi Geografis Penentuan Wilayah Rawan Banjir di Kabupaten Buleleng - Komang Ika Hendriana; I Gede Adi Saputra Yasa; Made Windu Antara Kesiman; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2013)
This study aims to (1) create a design andimplementation of geographic information systems (GIS) todetermine flood-prone areas in Buleleng regency (2) to analyzefactors such as rainfall causes flooding, land use and topographyusing GIS to determine areas prone flooding in Buleleng regency.SIG design is the determination of flood-prone areas describedusing UML (Unified Modeling laguage). The process ofdetermining the flood-prone area analysis is done by providing theweighting of each factor causing floods in Buleleng, ie rainfall,land use, and topography. Weights given by the size of the effect isgiven to flooding. The greater influence of these factors on theoccurrence of floods, then the greater weight given.The final result of the analysis process with the weightingfactor is the flood zone classification of flood vulnerability that isdivided into four levels, namely grim prone, prone, prone enough,and safe. Of the four levels of the results are displayed in the formof thematic maps flood vulnerability areas in Buleleng. From theresults of testing both structural and functional systems generatedthat the system is capable of running in accordance with theexpected results that produce flood vulnerability information in theform of thematic maps flood vulnerability.